Synthesis of Diporphyrins by Oxidative Coupling with Pd(TFA)2-Cu(OTf)2 under Ball-Milling Conditions - Lu, Xiuqiang; Chen, Guofen; Li, Fei (Synthesis, 2021)
A sustainable synthetic method for the synthesis of diporphyrins under ball-milling conditions is reported. The meso-meso linked diporphyrins are efficiently accessed by direct oxidative homo-coupling of porphyrins with Pd(TFA)2 as the catalyst and Cu(OTf)2 as the oxidant.
Keywords: diporphyrins; oxidative coupling; sustainable chemistry; ball-milling; mechanochemistry